Ensino de língua portuguesa para estudantes surdos: uma revisão bibliográfica na educação - Machado, Gisele do Amaral (Universidade Federal de São Carlos, 2020)
The research seeks to survey scientific productions produced from 2009 to 2019 starting with the publication of National Policies for Special Education from the perspective of Inclusive Education. The search took place within the databases of the National Association of Graduate Studies and Research in Education (ANPEd) and Scientific Electronic Library Online (SciELO), seeking to analyze, reflect and discover which publications relate the learning of Portuguese language by deaf people, as well as discover which publications bring pedagogical practices. In total, ten articles were published from 2009 to 2019. As a result, SciELO found only three publications that briefly contained some pedagogical practice that could contribute to the learning of the second language (as mentioned in Decree 5.626 / 05). In the ANPEd database only one publication. In total, four publications address educational issues. How others emphasize the challenges of inclusion / exclusion. They report the challenges of acquiring Sign Language as a first language and thus structuring for the learning of the Portuguese (written) language. Thus, it is clear that only public policies that guarantee the rights of deaf people are not enough. There must be structures that ensure that the legislation is actually enforced and the rights of deaf people are guaranteed, especially when the acquisition of the Portuguese language in written form is actually implemented.
Portuguese language teaching for deaf students: a bibliographic review in education
Keywords: Educação de surdos; Práticas pedagógicas; Língua Portuguesa; CIENCIAS HUMANAS::EDUCACAO